Assessment of smartphone usage among students for effective learning during Covid-19 pandemic lockdown in senior secondary schools in Ogun State, Nigeria - Sina , Ayelaagbe, O.; Ahmed, Kareem, I. (Kashere Journal of Education, 2023)
This paper assessed the use of smartphone for effective learning during Covid-19 pandemic lockdown among senior secondary schools in Ogun State. It compared the difference that exists between the gender, age and location of the students during Covid-19 lockdown. The study was conducted using a descriptive research method. Three (3) research questions and hypotheses were formulated and one hundred and fifty (150) respondents were sampled using simple random technique. The instrument for data collection was researcher’s designed questionnaire. Five (5) experts in the field of Educational Technology validated the0 instrument to ensure content and face validity of the instrument. Cronbach’s Alpha was used to find out the value of the reliability of the instrument and it yielded 0.80. Data collected were analyzed using mean, standard deviation and ANOVA to test the hypotheses formulated at 0.05 significance. The study concluded that smartphone can be effectively use for learning regardless of the gender, age and locations. It was therefore recommended that curriculum planners should incorporate the use of smartphone into the school curriculum and that the government should provide necessary facilities and infrastructures for the use of smartphones in schools.